THE ANISOTROPIC SEISMIC STRUCTURE OF THE EAST EUROPEAN PLATFORM - Matzel E.; Grand S.P. (My University, 2004)
We present models for the P and S velocity structure of the upper mantle beneath the East European platform including measurements of radial anisotropy. The models were obtained by full waveform inversion of 3-component broadband seismograms from strike-slip earthquakes located near the edge of the platform and recorded in Russia and Europe. We used direct and multiply reflected body wave arrivals (S, SS, P, PP) combined with fundamental mode Love and Rayleigh waves at source-receiver distances between 15° and 50° to resolve mantle structure down to the 410 km discontinuity. The platform is underlain by a radially anisotropic mantle lid extending to a depth of 200 km with a largely isotropic mantle below. The model has a positive velocity gradient from 41 km to 100 km depth, and a relatively uniform velocity structure from 100 km to 200 km depth with high SH and PH velocities (4.77 km/s, 8.45 km/s). Shear anisotropy is uniform at 5% (βH > βV) from 41 to 200 km depth, drops to 2% from 200 to 250 km and is isotropic below that. The average shear velocity from 100 to 250 km is also uniform at 4.65 km/s and the drop in anisotropy is matched by a drop in βH to 4.70 km/s combined with an increase in βV to 4.60 km/s. Below 250 km there is a positive velocity gradient in both P and S velocity down to 410 km. P anisotropy is not well resolved, but P structure mimics the SH velocity structure, suggesting that P is also anisotropic within the lid.
Keywords: anisotropy; inversion; mantle; Europe